Pengaruh Pajak Daerah, Retribusi Daerah, Laba BUMD, Lain-Lain yang Sah Terhadap Pertumbuhan Ekonomi - Aenun Siri; Muhammad Ridwan (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
This study aims to determine the effect of local taxes, regional levies, BUMD profits, other legitimate PAD on economic growth empirical studies at district and city BPS in Banten Province in 2016-2020. This type of research is quantitative research. the dependent variable used in this study is economic growth and the independent variables in this study are local taxes, regional levies, BUMD funds and other legitimate PAD. The research used in this study is the district / city in BPS (Central Bureau of Statistics). The data analysis used is panel data regression analysis. The cross section data in this study were 8 districts/cities in the province of Banten and the time series data in this study was from 2016 to 2020 using the saturated sample method. All data used were entered in a computer statistical program, namely E-Views 9 for testing. The results of the study can be concluded that local taxes, regional levies, BUMD profits and other legitimate PAD simultaneously have a significant effect on economic growth in Banten Province 2016-2020. The results of the study show that significantly local taxes, regional levies, BUMD profits and other legitimate PAD have no effect on economic growth.